Lyde Green Roman Villa, Emersons Green, South Gloucestershire - Hobson, Matthew S.; Newman, Richard (2021)
The Roman villa at Lyde Green was excavated between mid-2012 and mid-2013 along with its surroundings and antecedent settlement. The results of the stratigraphic analysis are given here, along with specialist reports on the human remains, pottery (including thin sections), ceramic building material, small finds, coinage and iron-working waste.